Komunikasi Internal Pengelola Program di Biro Umum Sekretariat Daerah Provinsi Jawa Barat dalam Membangun Partisipasi Pegawai pada Program Poe Ibu - Zahra Kartika Fauziyah; Nantia Rena Dewi Munggaran; Rezsa Yushar Diansyah (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
Voluntary participatory programs in government organizations depend heavily on the quality of internal communication to sustain employee engagement without administrative mandates. This study examined the internal communication of program administrators at the General Bureau (Biro Umum) of the Regional Secretariat of West Java Province in building employee participation in the Gerakan Rereongan Sapoe Sarebu Program (Poe Ibu), a voluntary daily donation initiative launched through Governor's Circular Number 149/PMD.03.04/KESRA on 1 October 2025. The study aimed to describe how internal communication operated across four goals of the Welch and Jackson (2007) Internal Communication Model: sense of belonging, employee voice, line management communication, and corporate integrity. A descriptive qualitative approach was employed within a constructivist paradigm. Data were collected through in-depth interviews, observation, and documentation involving seven purposively selected informants, comprising three program administrators, two participating employees, and two non-participating employees. The findings revealed that sense of belonging was built through voluntary framing grounded in gotong royong values and Sundanese local wisdom, yet did not automatically lead to active participation. Barriers to employee voice stemmed from hierarchical culture creating psychological pressure to remain silent, not from the absence of channels. Department heads proved more influential than all formal communication channels in sustaining participation consistency. Layered transparency-built employee trust, yet trust was found to be a necessary but not sufficient condition for participation. Overall, the success of internal communication in voluntary bureaucratic programs was not determined by the number of available channels, but by the organization's ability to build meaning that touches employees' identity, psychological safety to speak, and trust grounded in consistency. The study recommended strengthening an inclusive communication climate, standardizing line management roles, and enhancing transparency reporting quality.